Reconstruction of the Limits of Criminalization of Unlawful Elements and Abuse of Authority to Achieve Legal Certainty in Enforcing Criminal Acts of Corruption - Rizal Syamsul; R Richard (Journal Customary Law, 2026)
This study aims to analyze the disharmony of norms and problems in the implementation of Article 2 paragraph (1) and Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, reconstruct the boundaries of criminal liability between administrative wrong and corruptive wrong, and formulate an ideal formulation of legal reform in the perspective of ius constituendum. The study uses a normative juridical method with a statutory and conceptual approach, through an analysis of laws and regulations, court decisions, criminal law doctrine, and government administrative law. The results of the study indicate that the main problem lies in the blurring of the boundaries between the elements of unlawfulness, abuse of authority, benefiting oneself or others, and state financial losses, which gives rise to overlapping crimes, disparity in decisions, and a tendency to criminalize administrative errors, official discretion, and business risks of BUMN/BUMD. This study found a reconstruction model in the form of a five-stage separation model, namely a tiered separation between procedural violation, administrative negligence, abuse of office, corrupt intent, and actual state loss as a normative threshold in determining the transformation of maladministration into criminal acts of corruption. Based on these findings, this study recommends a reformulation of Article 2 focused on unlawful enrichment based on wederrechtelijkheid, and Article 3 which is limited to abuse of authority based on deviation from the purpose of authority, elements of intent, and actual state losses, with harmonization with Law Number 30 of 2014 concerning Government Administration and strengthening safe harbor for official discretion and business decisions of State-Owned Enterprises/Regional-Owned Enterprises. The novelty of this study lies in the normative model of criminalization limitations that provides legal certainty in distinguishing administrative errors and criminal acts of corruption, while simultaneously strengthening the effectiveness of corruption eradication law reform in Indonesia.